Mastering Linux Command Line - Brain, www.GlobalETraining.com (Packt Publishing, 2020)
Develop the most in-demand skills for DevOps and cloud professionals About This Video Learn the Linux command line from scratch Browse the Linux filesystem efficiently Create your own commands to save time In Detail Most businesses are now migrating to Cloud and other cloud-related technologies, making Linux command line expertise a must-have skill for DevOps and cloud engineers. This course will teach you the fundamentals of the Linux command line through an enjoyable learning experience. It includes some interesting videos that will guide you in setting up your own Linux VM and a Linux EC2 instance in the AWS cloud. This hands-on course will help you master the Linux command line with bite-sized videos that guide you at every step. You'll learn to work with files and folders, understand the Linux filesystem layout, and navigate through the filesystem efficiently. You'll get to grips with topics such as Linux permissions, hard and soft links, and text processing commands. As you advance, you'll cover standard I/O and redirection and learn to compress and uncompress files and folders. The course will also take you through sudo, Vi editor, scheduling jobs using cron, customizing a bash environment, and much more!